Visual tools for developing cross-disciplinary collaboration, innovation and entrepreneurship capacity - Griffith, Selena; Carruthers, Kate; Bliemel, Martin, Dr (Transformative pedagogies in the visual domain, 2018)
"Visual Tools for Developing Cross-Disciplinary Collaboration, Innovation and Entrepreneurship Capacity will identify and document pedagogical and practice-based visual approaches to scaffold and develop capacity for cross-disciplinary collaboration, innovation and entrepreneurship. An introductory chapter will introduce and contextualise the key themes of the book. It outlines the value in supporting acquisition of cross-disciplinary collaboration, innovation and entrepreneurship skills in students and why visual tools are particularly useful in doing this. The main body of the book will be divided into four sections, each will include theory and case study based inquiries. - Visual Tools for Collaboration This first section would explore approaches to developing skills for cross-disciplinary collaboration in students leveraging visual tools and artefacts. - Visual tools for Innovation This second section would explore approaches to scaffolding the acquisition of innovation skills in students via use of visual tools and artefacts. - Visual tools for Entrepreneurship This third section would explore how students can be supported and encouraged to attain appropriate skills and knowledge for successful entrepreneurship through the use of visual tools and artefacts. - Integrated Approaches This fourth, and final, section will demonstrate integrated approaches with respect two or three of these. The chapter authors have been selected from across disciplinary specialisations from a global pool of educators and practitioners in order to provide a broad range of perspectives. A final summary chapter summaries and reflects on the key insights of the book"--